Penyelenggaraan Angkutan Barang Program Tol Laut Konektifitas - Prasetyawati, Indah (Direktorat Jenderal Anggaran Kementerian, Keuangan Republik Indonesia, 2024)
As an archipelagic country, in an effort to boost the national economy, equalize the economy and reduce economic inequality between the western and eastern regions, the Government, by carrying the context of Nawa Cita, launched a program entitled: